2016
DOI: 10.1093/ndt/gfw029
|View full text |Cite
|
Sign up to set email alerts
|

Mild prolonged chronic hyponatremia and risk of hip fracture in the elderly

Abstract: Mild prolonged chronic hyponatremia is independently associated with hip fracture risk in the elderly population, although the absolute risk is low. However, proof that correcting hyponatremia will result in a reduction of hip fractures is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 33 publications
3
65
3
4
Order By: Relevance
“…This seems consistent with data on previous studies indicating significant changes in BMD via alendronate treatment at the 6 th and 12 th month of therapy (22,23), as well as efficacy of alendronate treatment on prevention of hip fractures in females with or without vertebral fractures starting from the 18 th month of therapy and being maintained for 36 months (24). In fact, although BMD is a strong predictor of fracture, most fractures occur in individuals without osteoporosis by BMD criteria (8). Hence, the likelihood of hyponatremia to lead to fractures through other effects on bone such as decreased bone quality, which is not captured by BMD, has also been emphasized (8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This seems consistent with data on previous studies indicating significant changes in BMD via alendronate treatment at the 6 th and 12 th month of therapy (22,23), as well as efficacy of alendronate treatment on prevention of hip fractures in females with or without vertebral fractures starting from the 18 th month of therapy and being maintained for 36 months (24). In fact, although BMD is a strong predictor of fracture, most fractures occur in individuals without osteoporosis by BMD criteria (8). Hence, the likelihood of hyponatremia to lead to fractures through other effects on bone such as decreased bone quality, which is not captured by BMD, has also been emphasized (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, albeit a comparatively little awareness, there is growing evidence that even a mild degree of chronic hyponatremia is associated with multiple clinically significant outcomes in the elderly population (2,8) in regards to immobility and falls (9), bone demineralization and osteoporosis (10), hip fractures (11), cognitive impairment (1) as well as hospital readmission and need for long-term care (12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests that the skin and the connective tissues may serve as a Na + storage, capable to release Na + in response to reduced intake by changing its polyanionic character [3]. In addition, several studies have recently shown that in both humans and animal models, chronic hyponatremia is associated with bone resorption and osteoporosis [4]. One possibility is that chronic hyponatremia may lead to sodium loss from the bones with consequent bone demineralization [5].…”
Section: Introductionmentioning
confidence: 99%